Longevity and germination of Juniperus communis L. pollen after storage - Andrej Kormuťák (Nature Portfolio, 2021)
Abstract Pollen storage belongs among the most important activities associated with pollen handling. It overcomes the differences in pollen shedding and ovule receptivity during controlled pollination experiments. It is especially important for species like common juniper (Juniperus communis L.) with an extremely low quality of seeds due to pollination failure. Additionally, it is a substantial part of germplasm preservation programmes in pollen banks. In the present paper, the effect of short-term storage of pollen was studied using pollen samples from five shrubs in an in vitro germination test. Two temperature regimes were tested. The pollen viability of freshly collected pollen varied considerably between individual shrubs, exhibiting 67.3–88.6% germination rate and 248.0–367.3 µm of pollen tubes. Storage at + 4 °C for four months was accompanied by a profound decline in pollen viability. The germination percentage was reduced to 49.2–75.2% and the pollen tube length to 32.5–69.0%, depending on individual shrubs. The corresponding decline in pollen viability characteristics during storage at − 20 °C was only negligible in two of the tested shrubs. In the remaining three shrub samples, an increase in germination percentage was observed. Pollen tube growth responded more sensitively to freezing, but, on average, the decrease in length was lower than that at + 4 °C. The rate of reduction in pollen tube length varied between 11.5 and 45.4%. Cytological events accompanying in vitro germination of freezer-stored pollen exhibited some delay in releasing the exine from pollen grains during the early stages of germination as compared with freshly collected pollen. In conclusion, short-term storage of the common juniper pollen in a freezer is better for the preservation of its viability than storage at + 4 °C.